REDUCTION PROPERTIES OF IRON ORE COMPOSITE PELLETS BEARING WASTE PLASTICS - Birol, Burak; Saridede, Muhlis Nezihi (JOHN WILEY & SONS, 2011)
Plastic wastes become a huge problem day after day due to the growth of plastic industry. Hence, plastic wastes are used as a raw material for other industries to eliminate this problem. Polyethylene Terephthalate (PET), which is a commonly used for plastic bottles, may be used as a reductant for iron production because of its C and H content. In this study, composite pellets containing iron ore concentrate, flux and reductant were prepared. Crystallized PET bottles and coke were used as reductant after ground. The prepared pellets were reduced at 1400 degrees C for 30 min. and iron nuggets were produced successfully. Usage of waste PET purely as reductant in composite pellets gives a higher metallization degree and proper carbon content than coke or PET and coke mixture.
Keywords: Composite pellet; reduction; plastics; PET; iron nugget; COAL; Materials Science; Metallurgy & Metallurgical Engineering; Mining & Mineral Processing